Pelatihan Pengolahan Produk Hasil Pertanian Organik pada Ibu-Ibu Kelompok Rumah Sayur SKM di Desa Somongari, Purworejo - Utami, Nurul Putrie; Sasongko, Hadi; Salamah, Zuhrotus; Purbosari, Purwanti Pratiwi (UKInstitute, 2022)
Organic agricultural products such as fresh vegetables is a product that is easily damaged and can cause losses if not utilized properly. Food processing is a way to increase the storage capacity of organic agricultural products. Instead of increasing storability of food, processing food products is also a choice to develop marketing of agricultural products. Therefore, the organic farming women as the members of the SKM (Suka Karya Makmur) Vegetable House Group was given training in the processing of organic agricultural products in the form of vegetable noodles, spinach chips, and vegetable sticks. The training activities were carried out using demonstration and simulation methods which were attended by 35 people. The team provides a demonstration with examples and then the participants simulate the processing of food products independently. Evaluation of activities is carried out by providing pre-test and post-test, observation, and interviews of participants. The result of this activity is an increase in knowledge, skills, and entrepreneurial interest from the members of the SKM Vegetable House Group. The training activity for the manufacture of organic agricultural products is the first step to improve the economic status of the community in Somongari Village.